INTERACTIONS BETWEEN GUT MICROBIOTA AND DEPRESSIVE AND ANXIETY DISORDERS: A COMPREHENSIVE REVIEW - Natalia Maria Leśniak; Klaudia Martyna Patrzykąt; Anna Maria Zakrzewska; Aleksander Midera; Julia Aleksandra Leśniak; Michał Borowski; Klaudia Elżbieta Niwińska; Julia Agnieszka Michalak; Monika Augustyn; Kinga Popielarska; Kacper Jaskulski (International Journal of Innovative Technologies in Social Science, 2026)
Background. Depressive and anxiety disorders are major challenges in modern medicine and are increasingly linked to gut dysbiosis. Evidence indicates that affected patients often exhibit reduced microbial diversity, lower levels of SCFA-producing bacteria, and increased pro-inflammatory taxa. Proposed mechanisms include altered SCFA production, neurotransmitter modulation, vagus nerve signaling, immune activation, HPA axis dysregulation, and impaired gut and blood–brain barrier integrity Aim. This review summarizes current evidence on the gut-brain axis and how it impacts mood disorders. Material and methods. The review analyzed English-language studies published between 2015 and 2025 using PubMed, SpringerLink, and Elsevier, focusing primarily on human research examining the gut microbiota, gut–brain axis, and their association with depressive and anxiety disorders. Results. The review highlights the potential of microbiota-based therapies for mood disorders. Probiotics, especially psychobiotic strains, show the most consistent benefits in reducing depressive and anxiety symptoms, while evidence for prebiotics and dietary interventions remains limited. Current studies are constrained by methodological heterogeneity, small sample sizes, and short intervention durations. Conclusions. Overall, accumulating data support the gut microbiota as a significant contributor to the development and modulation of depressive and anxiety disorders. While definitive clinical recommendations cannot yet be made, microbiota modulation represents a promising avenue for future integrative treatment approaches and warrants further rigorous investigation.